Adsorption of Heavy Metals from Contaminated Water using Leachate Modular Tower - Frank Aneke; Joy Adu (Salehan Institute of Higher Education, 2023)
The heavy metals (HMs) and metalloids such as Cr(VI), As(Ill), and Pb(II) in contaminated water are toxic even at trace levels and have caused devastating negative health impacts on human beings. Hence, the effective adsorption of these heavy metals from contaminated water is important to protect biodiversity, hydrosphere ecosystems, and human beings. In this study, a leachate modular tower (LMT) was developed for the singular purpose of adsorbing HMs. The LMT contained nano-slag as a liner, which was synthesized from slag. The nano-slag was blended in different proportions of 90:10; 80:20, 70:30, 60:40, and 50:50 to the combined mass of clay and nano-slag, to evaluate the most efficient ratio of the blends capable of adsorbing HMs and metalloids with 100% efficiency. A series of leachate tests were performed to evaluate the adsorption capacity of LMT with different embedded liners. Attenuation periods of 2, 5, 7, and 10 days with a temperature of 500 °C were also selected to improve the sorption rate and uptake of HMs. Subsequently, the effluents were subjected to inductive coupled plasma mass spectrometry (ICP-MS) tests to evaluate the concentrations and percentages of adsorbed HMs, which were calculated using a pseudo-first-order adsorption model. The results revealed that the removal of 98%As, 99%Cd, and 99.9% Pb was achieved with a 50%:50% ratio of soil and nano-slag as the liner at 10 days equilibrium period. Furthermore, 98%Zn, 95.45%Cu, 93.3%Fe, 97%Ni, and 89% Hg were achieved upon further investigation using the same dosage of soil and nano-slag and equilibrium conditions. The scanning electron microscopy (SEM) tests demonstrated that some traces of the absorbed HMs and metalloids were found on the liner surfaces, indicating significant changes in microstructure. The results indicated the sorption rate increased significantly due to the elevated temperature, aluminosilicate structure, and prolonged attenuation period, which are also associated with an elevated pH level and higher cation exchange capacity (CEC), of the liner. Doi: 10.28991/CEJ-2023-09-06-017 Full Text: PDF